CFD numerical simulation, verification with experimental results and internal flow analysis of bristle turbines - Sun Sheng Yang; Dong Ya Li; David Kupka; Jan Kolonicny; Punit Singh (Case Studies in Thermal Engineering)
In industrial facilities, a considerable amount of waste heat is often generated. However, due to the high costs associated with traditional methods of recovery, which do not align with the economic interests of enterprises, this waste heat is frequently wasted. With technological advancements, the bristle turbine has been proposed as a solution capable of effectively managing waste gases and providing added value to enterprises. Its advantages lie in its simple structure, easy installation, low rotational speed, and high reliability, offering a new option for waste heat recovery and utilization. Despite its potential, no previous research has conducted a detailed simulation of the bristle turbine, particularly focusing on internal flow dynamics, energy loss mechanisms, drag forces, and entropy generation. This study is the first to explore these critical aspects, making a novel contribution to the field. The paper presents the computational fluid dynamics (CFD) simulation of a 20 kW bristle turbine. The numerical simulation results are in good agreement with experimental results. Subsequently, the isentropic efficiency of the turbine at different speeds is simulated, and the performance of the turbine under off-design conditions is analyzed. By investigating the energy loss mechanisms within the turbine, optimization designs are proposed.